Migratory connectivity of Blue-winged Teal: risk implications for avian influenza virus introduction to Cuba - Rodríguez-Ochoa, Alejandro; Kusack, Jackson W.; Mugica, Lourdes; Cruz, Martín Acosta; Alfonso, Pastor; Delgado-Hernández, Beatriz; Abreu, Yandy; García, Efren; Hobson, Keith A. (Frontiers in Bird Science, 2024)
Despite the clear threat of Avian Influenza Virus (AIV), surveillance programs in wild birds are scarce in Latin America and the Caribbean. Migratory connectivity analysis in birds can provide information about virus circulation. Our objective was to determine migratory connectivity of Bluewinged Teal and evaluate the risk of AIV introduction to Cuba by this species. The stable hydrogen isotope (δ 2 H) value in flight feathers was analyzed. Individuals were sampled during the migratory season of 2021 (N=126) and winter residence of 2020 (N=152), in western and central Cuba, respectively. Based on banding records from 1955 to 2018, the transition probabilities from 3 breeding areas in North America to 9 wintering areas was estimated with a Burnham's live-recapture dead-recovery modeling framework. Evidence of an age-related and phenological pattern in migratory origins was identified. A map of likely origin in North America of the individuals sampled for each season was generated, combining the isotopic information and transition probabilities. Individuals harvested in the migratory season in western Cuba were most likely from molt or natal areas in the prairies and forest regions from United States and southern Canada. Alternatively, individuals harvested in winter in the center of Cuba had the most likely origin in the U.S. prairie region. The spatial-temporal pattern of AIV prevalence in the estimated region was analyzed and suggestions are made to assist the Cuban system of active AIV surveillance of wild birds.